Gross Motor Function after Rehabilitation with the Atlas 2030 Pediatric Exoskeleton in Children With Cerebral Palsy - García Oliveros, Irma; Meabe Iturbe, Nerea; Marín Ojea, Juan Ignacio; Lancho Poblador, Carolina; Fuentes-Claramonte, Paola; Quemada Ubis, José Ignacio (Revista de neurologiá, 2025)
Introduction and Objectives: To evaluate the impact of intensive gait training on gross motor function using the pediatric exoskeleton ATLAS 2030, as well as to determine the post-intervention maintenance of effects in children with cerebral palsy (CP). Subjects and Methods: A non-randomized controlled prospective study. Thirteen children with CP participated. A program of four weekly sessions lasting 65 minutes each was implemented over six weeks. Gross motor function was assessed using the 88 items Gross Motor Function Measure (GMFM-88); physical exercise endurance was measured with the Six-Minute Walk Test (6MWT) using the device; the number of steps walked in each session and mode of use was recorded to evaluate adaptation to the activity. Three evaluations were conducted: before treatment, at the end of treatment (6 weeks), and a follow-up evaluation at 12 weeks. Results: The total GMFM-88 score showed significant changes at the end of the intervention (p < 0.001), which persisted at follow-up (p < 0.001). The number of steps in automatic and active modes increased significantly after the intervention (p < 0.001) and were maintained at follow-up (p = 0.001). Lastly, the 6MWT improved significantly after the intervention, with a reduction observed at follow-up (p < 0.001). Conclusions: Six weeks of intensive training with ATLAS 2030 positively impacts the gross motor function of children with CP, with benefits increasing six weeks after treatment completion. Physical endurance and adaptation to the activity improve with continued use. These results support the potential of ATLAS 2030 as an intensive therapeutic strategy for this population. Clinical Trial Registration: No: NCT07066956. https://clinicaltrials.gov/search?cond=NCT07066956.